2009
DOI: 10.1590/s1807-59322009001000006
|View full text |Cite
|
Sign up to set email alerts
|

Combining Cognitive Screening Tests for the Evaluation of Mild Cognitive Impairment in the Elderly

Abstract: OBJECTIVETo determine the accuracy of the Mini-Mental State Examination combined with the Verbal Fluency Test and Clock Drawing Test for the identification of patients with mild cognitive impairment and Alzheimer’s disease (AD).METHODThese tests were used to evaluate cognitive function in 247 older adults. Subjects were divided into three groups according to their cognitive state: mild cognitive impairment (n=83), AD (n=81), cognitively unimpaired controls (n=83), based on clinical and neuropsychological data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 42 publications
1
25
0
8
Order By: Relevance
“…That study demonstrated the importance of evaluating cognition in elderly populations using batteries with good construction and valid criteria. Ladeira et al 14 showed that a combination of screening tools, such as the MMSE, verbal fluency and CDT, was not useful for identifying cases of AD or MCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That study demonstrated the importance of evaluating cognition in elderly populations using batteries with good construction and valid criteria. Ladeira et al 14 showed that a combination of screening tools, such as the MMSE, verbal fluency and CDT, was not useful for identifying cases of AD or MCI.…”
Section: Introductionmentioning
confidence: 99%
“…The studies conducted by both Paula et al 13 and Ladeira et al 14 did not include memory tasks. Diniz et al 9 included a very short memory task that did not evaluate either retention over time or delayed recall.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizados sozinhos ou combinados, apenas esses testes não têm a capacidade de diagnosticar e diferenciar, com acurácia, CCL de sujeitos saudáveis. Além destes é importante que haja outros instrumentos mais específicos como escalas funcionais, além de também informações clínicas e resultados laboratoriais e de neuroimagem (Ladeira, Diniz, Nunes & Forlenza, 2009). A utilização de técnicas de neuroimagem são ferramentas essenciais na avaliação geral de sujeitos com CCL, devido à importância na identificação de causas específicas e tratáveis de declínio cognitivo, como tumores, aumentos de pressão e hematomas, entre outros.…”
Section: Definição De Comprometimento Cognitivo No CCLunclassified
“…Diversos autores (Winblad et al, 2004;Yassuda et al, 2008;Petersen et al, 2009;Ladeira, Diniz, Nunes & Forlenza, 2009;Clark et al, 2011;Damin, 2011;Frota et al, 2011;Forlenza et al, 2013;O'Caoimh et al, 2013;Paula et al, 2013;Petersen et al, 2014) (Manly et al, 2005;Yaffe et al, 2011;Ganguli et al, 2011;Charchat-Fichman et al, 2013) comprometimentos na memória e na função executiva são suficientes para considerar CCL, além de designar subtipos específicos como CCLa e CCLd.…”
Section: Problemas Metodológicos No Uso Dos Testes Cognitivos No Diagunclassified
See 1 more Smart Citation